Educational Differences in Mortality and Hospitalisation for Cardiovascular Diseases for Males - Govert Bijwaard (Institute of Labor Economics (IZA), 2021)
High educated individuals are less frequently admitted to hospital for cardiovascular diseases and live longer than the lower educated. We address whether the educational gradient in the mortality rate can be explained by the educational difference in the timing of CVD hospitalisation. We account for possible selective hospitalisation, by using a correlated multistate hazard model (a 'Timing-of-events'- model) and, for selection into education, by using inverse propensity weighting based on the probability to attain higher education. We use Swedish Military Conscription Data (1951-1960), for males only, linked to administrative Swedish registers. Our empirical results indicate a clear educational gradient in mortality and in the impact of CVD hospitalisation on mortality. The implied educational gain in the number of months lost is, however, mainly due to other factors than CVD hospitalisation. Extending the analysis to cause specific mortality reveals that the largest educational differences exist in death due to external causes.
Keywords: C41; I14; I24; 330; timing-of-events; CVD hospitalisation; mortality; education; inverse propensity weighting